Evaluation of microsatellite markers for selection of crossbred cattle - Naicy Thomas (Department of Animal Breeding and Genetics, College of Veterinary and Animal Sciences, 2005)
The possibility of using the informations of the allele frequency, genotype frequency, heterozygosity and PIC of five selected microsatellite markers (ILSTS096, HUJII77, BL41, BM1508 and BM4305) and their associations with the economically important traits for the selection of crossbred cattle were studied. Among the economic traits studied milk fat percentage and AFC showed significant difference among the ten sire families and hence their associations with the selected microsatellite markers were worked out. PCR conditions were standardised for each marker separately. The number of alleles, size range and number of genotypes identified were 12, 188-212 bp and 35 respectively for ILSTS096 locus, 13, 193-221 bp and 36 for HUJII77 locus, 14, 232-266 bp and 36 for BL41 locus, 7, 103-115 bp and 17 at BM1508 locus and 12, 146-168 bp and 37 for BM4305 locus in the unrelated crossbred dairy cattle population. The highest direct count heterozygosity was obtained for ILSTS096 followed by BL41, BM4305, HUJII77 and BM1508 (0.877-0.683). The highest unbiased heterozygosity was obtained for ILSTS096 followed by BL41, BM4305, HUJII77 and BM1508 (0.880-0.686). All the markers were highly informative as their PIC values (0.865-0.630) were more than 0.5. Three sire families namely, Deva, Bull No.250 and Hakkim showed significantly lower milk fat percentage and three other (Dipesh, Onkar and Gopal), showed significantly higher AFC. All the five microsatellite markers had significant effect on milk fat percentage and three of them (ILSTS096, BL41 and BM4305) showed significant effect on AFC. The allelic averages of fat percentage for the allele 188 and 204 at ILSTS096 locus, 205 at HUJII77 locus and 154 at BM4305 locus were significantly lower and that of 198 at ILSTS096 locus, 240 at BL41 locus, 109 and 113 at BM1508 locus and 166 at BM4305 locus were significantly higher. The allelic averages of AFC for the alleles 196 at ILSTS096 locus, 246 at BL41 locus and 154 at BM4305 locus were significantly lower. All these three alleles were absent in the sires of the three families having higher AFC. The allelic frequencies of 188 and 204 of the marker ILSTS096 were low in the population and that of 198 was high. So selection against the alleles 188 and 204 and selection for the allele 198 can be done, but the impact of selection will be meagre. At the BL41 locus, frequency of the allele 240 was comparatively low and the frequency of the allele 242 is very high in the population. So the selection for the allele 240 and selection against the allele 242 will have good impact on milk fat percentage of the selected animals. Frequency of allele 246 in the population is comparatively low. Hence selection for this allele will be favourable to reduce the AFC. The frequency of the allele 109 of BM1508 is low. So selection for this allele will be more beneficial. The animals with the allele 166 at BM4305 locus had the highest average of milk fat percentage and the frequency of this allele in the population is very low, hence selection for this allele will have good impact on higher milk fat percentage.